Prognostic significance of ERCC1, RRM1 and BRCA1 in surgically-treated patients with non-small cell lung cancer - Pesta, Martin; Kulda, Vlastimil; Fiala, Ondrej; Safranek, Jarmil; Topolcan, Ondrej; Krakorova, Gabriela; Cerny, Radim; Pesek, Milos (Anticancer research, 2012)
UNLABELLED: Chemotherapy is an important modality of treatment for non-small cell lung cancer (NSCLC). Recent studies have shown that assessment of predictive molecular markers could be helpful for estimation of the response rate to chemotherapy. The aim of our study was to assess the relation of mRNA levels of DNA repair genes excision repair cross-complementary group 1 (ERCC1), ribonucleotide reductase subunit M1 (RRM1) and breast cancer 1 (BRCA1), in surgically-resected tumor tissues from patients who underwent adjuvant chemotherapy, to the disease-free interval (DFI) and overall survival (OS). We investigated if potential residual tumor cells after resection reflect properties of the primary tumor and response to chemotherapy according to the level of predictive markers with respect to current knowledge. PATIENTS AND METHODS: We studied a group of 90 patients with NSCLC who had undergone curative lung resection; 59 of them were subsequently treated with adjuvant chemotherapy, DFI and OS were evaluated only in this subgroup. Quantitative estimation of mRNA of selected genes in paired (tumor and control)-lung tissue samples was performed by real-time reverse transcription-polymerase chain reaction (RT-PCR). RESULTS: We found a significantly lower mRNA expression of ERCC1 (p<0.001) and RRM1 (p=0.023) in NSCLC tumor tissues compared to normal lung tissues. Comparing expression in histological subtypes, we recorded higher mRNA expression of ERCC1 (p=0.021), RRM1 (p=0.011) and BRCA1 (p=0.011) in adenocarcinoma than in squamous cell carcinoma (SCC). Differences in DFI and OS were found only in specific subgroups according to tumor type and stage. We found longer OS for patients with adenocarcinoma with higher expression of the RRM1 mRNA (p=0.002), and for patients with SCC with higher expression of the BRCA1 mRNA (p=0.041). In patients with NSCLC of stage III, we found longer DFI in those with higher expression of RRM1 (p=0.004) and ERCC1 (p=0.038). CONCLUSION: Patients who had been treated with adjuvant chemotherapy and had shown lower expression of repair genes had adverse prognosis. We observed that the assessment of DNA repair gene level in primary tumors treated by surgical resection had prognostic significance and did not predict response to adjuvant chemotherapy.
Keywords: senioři; proporcionální rizikové modely; Ribonucleoside Diphosphate Reductase; messenger RNA; Proportional Hazards Models; DNA-Binding Proteins; Real-Time Polymerase Chain Reaction; senioři nad 80 let; Prognosis; endonukleasy; mužské pohlaví; nádory plic; kvantitativní polymerázová řetězová reakce; Biomarkers, Tumor; polymerázová řetězová reakce s reverzní transkripcí; Aged, 80 and over; Neoplasm Staging; nemalobuněčný karcinom plic; nádorové biomarkery; ženské pohlaví; prognóza; nádorové supresorové proteiny; Humans; ribonukleosiddifosfátreduktasa; RNA, Messenger; Carcinoma, Non-Small-Cell Lung; Tumor Suppressor Proteins; Antineoplastic Combined Chemotherapy Protocols; DNA vazebné proteiny; staging nádorů; Reverse Transcriptase Polymerase Chain Reaction; protokoly protinádorové kombinované chemoterapie; BRCA1 Protein; protein BRCA1; Female; Aged; Lung Neoplasms; lidé; Male; Endonucleases